O Programa REUNI e os impactos produzidos no campus Ponta Grossa da Universidade Tecnológica Federal do Paraná - Zander, Tatiane Marisa Marafigo (2023)
The present study aimed to assess the impacts of the Program for Support of Federal Universities Restructuring and Expansion Plans (Reuni) at the Ponta Grossa Campus of the Federal Technological University of Paraná (UTFPR). This was a field research with a qualitative approach to the problem. The research corpus was composed of documents from Reuni, UTFPR, and interviews. The analytical procedure used in the interviews was content analysis. It was found that the Ponta Grossa Campus fulfilled most of the commitments made in the Reuni agreement, particularly regarding the expansion of undergraduate vacancies, the opening of new undergraduate and graduate courses, the update and expansion of the campus infrastructure, and the acquisition of new equipment. The number of staff allocated to the campus was also higher than initially foreseen. The unfulfilled commitments were related to student attrition and retention. It is concluded that the impacts of the Ponta Grossa Campus' participation were much more positive than negative.